2021
DOI: 10.5812/numonthly.113990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetylcysteine on hsCRP in Patients on Continues Ambulatory Peritoneal Dialysis: A Quasi-Experimental Study

Abstract: Background: Inflammatory processes are proved in patients with chronic kidney disease (CKD) as one of the leading causes of mortality and morbidity. N-acetylcysteine (NAC) is known as an antioxidant drug with anti-inflammatory effects. Objectives: This study aimed to evaluate the effects of NAC on hsCRP in CKD patients on peritoneal dialysis. Methods: This quasi-experimental self-controlled study examined adult CKD patients on peritoneal dialysis referred to the peritoneal dialysis clinic. The participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Castor oil, NAC, and magnesium sulfate (MgSO 4 ) were the most frequent treatment in patients with ALP poisoning. Large amounts of sodium bicarbonate (NaHCO 3 ) are recommended for correction of acidosis in ALP poisoned patients, but there is some controversy about its effectiveness [12,13,30,45]. We found that taking sodium bicarbonate (NaHCO 3 ) in ALP poisoned patients is one of the main prognostic factors for in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Castor oil, NAC, and magnesium sulfate (MgSO 4 ) were the most frequent treatment in patients with ALP poisoning. Large amounts of sodium bicarbonate (NaHCO 3 ) are recommended for correction of acidosis in ALP poisoned patients, but there is some controversy about its effectiveness [12,13,30,45]. We found that taking sodium bicarbonate (NaHCO 3 ) in ALP poisoned patients is one of the main prognostic factors for in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A placebo-controlled study in PD patients found that oral intake of 600 mg of NAC twice daily for 8 weeks resulted in decreased plasma levels of IL-6 compared to controls [ 117 ]. Similarly, the administration of oral NAC significantly decreased hs-CRP levels in PD patients; this anti-inflammatory effect was more pronounced in patients with increased inflammatory status at baseline (CRP levels between 5 and 15 mg/L) [ 118 ]. Another placebo-controlled trial also examined the effect of NAC on inflammation status of chronic ambulatory PD subjects demonstrating that oral NAC administration (600 mg of NAC twice daily for 8 weeks) reduced the levels of several inflammatory biomarkers; interleukin 1 (IL-1), IL-6, hs-CRP, procalcitonin, complement C3, TNF-a and soluble intercellular adhesion molecule-1 (SICAM-1) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%